Antimicrobial Potential of Phytochemicals from Coccinia grandis Leaves: A Molecular Docking Study Against Penicillin-Binding Protein 5 of Escherichia coli and DNA Topoisomerase IV Subunit B (ParE 24kDa) of Staphylococcus aureus and Escherichia coli - Isuranga, Malshan; Danthanarayana, Dulki Nihinsa (Biology, Medicine, & Natural Product Chemistry, 2025)
Coccinia grandis (C. grandis) leaves, traditionally used in Sri Lanka for diabetes management, also have a potential antimicrobial activity. In this study, site-specific molecular docking was performed to investigate the antimicrobial activity of phytochemicals of Coccinia grandis leaves against Penicillin-binding protein 5 (PBP 5) and DNA topoisomerase IV subunit B (ParE 24kDa) of Escherichia coli (E. coli) and DNA topoisomerase IV subunit B (ParE 24kDa) of Staphylococcus aureus (S. aureus). Penicillin was selected as the reference molecule for Penicillin-binding protein 5 and for DNA topoisomerase IV subunit B (ParE 24kDa), Novobiocin was selected as the reference molecule. The results identified Lupeol (-7.72 kcal/mol) and Beta-Sitosterol (-8.21kcal/mol) have a higher binding affinity to PBP5 of E. coli than Penicillin (-7.20 kcal/mol). Quercetin (-6.70 kcal/mol), Kaempferol (-6.95 kcal/mol), Naringenin (-7.07 kcal/mol), Isoquercetin (-6.15 kcal/mol), Lupeol (-7.87 kcal/mol), Beta-Sitosterol (-9.42 kcal/mol) and Sanguinarine (-9.07 kcal/mol) show higher binding affinity to DNA topoisomerase IV subunit B (ParE 24kDa) of S. aureus than novobiocin (-6.04 kcal/mol). As well Quercetin (-6.85 kcal/mol), Kaempferol (-6.82 kcal/mol), Naringenin (-7.23 kcal/mol), Isoquercetin (-6.20 kcal/mol), Lupeol (-7.67 kcal/mol), Beta-Sitosterol (-9.08 kcal/mol) and Sanguinarine (-9.03 kcal/mol) show higher binding affinity to DNA topoisomerase IV subunit B (ParE 24kDa) of E. coli than novobiocin (-5.76 kcal/mol). In silico pharmacokinetic and physicochemical parameter predictions were also conducted to study drug-likeness of above molecules using specialized web servers.